2014
DOI: 10.1117/1.jbo.19.11.117003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of noninvasivein vivomelanoma and nonmelanoma skin cancers using multimodal spectral diagnosis

Abstract: Abstract. The goal of this study was to determine the diagnostic capability of a multimodal spectral diagnosis (SD) for in vivo noninvasive disease diagnosis of melanoma and nonmelanoma skin cancers. We acquired reflectance, fluorescence, and Raman spectra from 137 lesions in 76 patients using custom-built optical fiber-based clinical systems. Biopsies of lesions were classified using standard histopathology as malignant melanoma (MM), nonmelanoma pigmented lesion (PL), basal cell carcinoma (BCC), actinic kera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 54 publications
2
108
0
Order By: Relevance
“…Since in situ constituents are extracted from skin in their natural state, without any further processing, they can better represent the skin microenvironment that cannot be recapitulated in a synthetic environment. Second, our model was validated by a previous in vivo clinical screening study [12] acquired by a Raman optical fiber probe [27]. Currently, the only biophysical Raman skin cancer model was based on excised fragments of BCC and melanoma skin tissues [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since in situ constituents are extracted from skin in their natural state, without any further processing, they can better represent the skin microenvironment that cannot be recapitulated in a synthetic environment. Second, our model was validated by a previous in vivo clinical screening study [12] acquired by a Raman optical fiber probe [27]. Currently, the only biophysical Raman skin cancer model was based on excised fragments of BCC and melanoma skin tissues [9].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo human skin spectra came from our previous skin cancer screening study [12]. Data were collected from an optical fiber probe [27] integrated in a multimodal spectroscopy system [28] on different sites, such as scalp, nose, earlobe, shoulder and thigh.…”
Section: Clinical Screening Data Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Zhao et al reported that the diagnostic specificity for fixed sensitivity of 0.99-0.90 was improved from 0.17-0.65 to 0.20-0.75 with wave-number selection based on a leave-one-out cross-selection procedure [13]. Lim et al suggested that a combination of three fiber-opticbased optical spectroscopy modalities (diffuse optical spectroscopy, laser-induced fluorescence spectroscopy, and Raman spectroscopy) is necessary for accurate and noninvasive diagnosis of both melanoma and non-melanoma skin cancers in vivo [14].…”
Section: Introductionmentioning
confidence: 99%